Investigation Into the Firing and Synaptic Properties of Motoneurons in Developing Zebrafish - Gaudreau, Stephanie (Université d'Ottawa | University of Ottawa, 2025)
Movement is the driving force of survival for many animals yet the full repertoire of movements an animal can produce is not present at birth. The study of motor maturation – how simple movements are turned into complex ones – is invaluable to our understanding of motor control by the nervous system. Uncovering how the neuromuscular system changes throughout development can reveal insights into fundamental principles and mechanisms underlying how movement is produced. This thesis leverages the accessibility of the neuromuscular system in developing zebrafish to 1) validate a screening method that makes use of optogenetics for the assessment of neuromuscular junction function in the context of disease, and 2) uncover the role of an ion current in network-wide and motoneuron-specific behaviour during motor maturation. We then identify for the first time the presence of a subthreshold non-inactivating potassium current known as the M-current (IM) in zebrafish spinal circuits for locomotion, revealing its role in regulating swimming episode and motor burst duration during fictive locomotion in spinalized animals. We further our investigation into the role of IM in the context of locomotion by revealing its role in the control of primary motoneuron excitability and regulation of repetitive firing. Moreover, we show that the magnitude of IM and the role it plays in primary motoneurons changes during early development. We also characterize developmental changes to the persistent sodium current (INaP), the L-type channel mediated calcium current (ICaL), and P/Q-type mediated calcium current (ICaP/Q) in primary motoneurons, emphasizing the contributions of INaP with IM to the control of repetitive firing. Finally, we investigate IM as a target of spinal neuromodulation during development and identify muscarine as an enhancer and serotonin via 5-HT1A receptors as an inhibitor of IM in primary motoneurons. Interestingly, we reveal that enhancement by muscarine and inhibition by 5-HT1A receptor signaling is not consistent across larval development but could be tied to developmental changes in IM. Our findings detail how several ion currents interact to shape motoneuron firing during development as motor maturation progresses. Our findings also reveal mechanisms by which ion currents in zebrafish motoneurons are differentially modulated during development, perhaps to facilitate motor maturation. This work highlights the intricacies of the expression, function, and modulation of the diverse ion currents expressed in motoneurons during development.
Keywords: zebrafish; spinal locomotor circuits; motoneurons; ion currents